Administrative Practices and Political Control in Anatolian and Syro-Anatolian Polities in the 2nd and 1st Millennium BCE - Mora, Clelia; Torri, Giulia (Studia Asiana, 2023)
This volume originates from a research project, which was funded within the PRIN program Writing Uses: Transmission of Knowledge, Administrative Practices and Political Control in Anatolian and Syro-Anatolian Polities in the 2nd and 1st Millennium BCE. The project involved 'research units' from different Italian universities (Torino, Pavia, Bologna, Firenze, Napoli - Suor Orsola Benincasa). The papers presented here, seek to fill some gaps in our knowledge of the Hittite Empire and its epigones, and offer an updated picture of some aspects of the Hittite and post-Hittite administration in Anatolia and Syria through the analysis and interpretation of epigraphic and archaeological evidence.